Integrated miRNA-mRNA transcriptomic analysis of hepatopancreas reveals molecular mechanisms in Macrobrachium rosenbergii under graded nitrite stress - Xilian Li; Haihua Cheng; Yunpeng Fan; Binpeng Xu; Yang Xu; Qiang Gao (PLoS ONE, 2026)
Nitrite accumulation poses a significant threat to aquatic organisms in intensive aquaculture systems. Macrobrachium rosenbergii , a commercially vital freshwater prawn, exhibits adaptive responses to environmental stressors, yet the molecular mechanisms underlying nitrite tolerance remain poorly understood. This study employed integrated mRNA and miRNA transcriptomics to dissect the regulatory networks activated in M. rosenbergii hepatopancreas under acute nitrite stress (0, 40, and 87.25 mg/L nitrite-N over 48 h). High-throughput sequencing revealed 640 and 912 differentially expressed genes (DEGs) in low-concentration (LC) and high-concentration (HC) groups, respectively, compared to controls (CK). In the LC group, enrichment was predominantly observed in ribosome biogenesis (96 genes, p < 0.001). Conversely, the HC group was characterized by the significant modulation of the PPAR signaling (11 genes), glycerophospholipid metabolism, and the citrate cycle ( p < 0.005). Calcium signaling and MAPK pathways may be central to stress adaptation across both groups. miRNA profiling revealed 17 downregulated and 2 upregulated miRNAs within the HC group relative to the CK group, with miR-193-y, miR-263-x, and miR-145-x implicated in metabolic regulation. Notably, novel miRNAs (e.g., novel-m0087-3p) showed concentration-dependent expression. qPCR validated the consistency of sequencing data, confirming stress-responsive genes ( P53 , HORMA , SLC25a28 ) and miRNAs. This study is the first to integrate the mRNA-miRNA regulatory network in Macrobrachium rosenbergii to elucidate the response mechanism to nitrite stress, emphasizing the role of metabolic reprogramming and signal pathway regulation as key survival strategies. It provides a foundation and novel perspectives for the molecular evolution of nitrite adaptability in aquatic animals and breeding programs.